High-throughput Platform for Screening Microbial Fuel Cell Components. (2017) - Vishwanathan, A.S.; Aiyer, Kartik S.; Sai, S. Siva Sankara; Rao, Govind
Abstract: We present a multi-anode microbial fuel cell configuration that simplifies the process of optimization of components and operating parameters. Working of the high-throughput screening platform has been described using four variables that are known to have a bearing on performance of microbial fuel cells.